Sistem Pengendali Energi Listrik Menggunakan Raspberry Pi Pada Smart Building Kampus - Masnur, Masnur; Marlina, Marlina (Forum Kerjasama Pendidikan Tinggi, 2022)
Electrical energy is a very important need that must be met for human needs, but the source of the power plant sometimes uses non-renewable natural resources. Savings in the use of electricity has an impact on the preservation of nature and the cost of electricity used. The problem is the waste of electricity use and the negligence of its users, such as not turning off electrical equipment or forgetting to leave the room. So